Development of Web-Module Enrichment Based on Scientific Approach on Plant Diversity Submaterial by Utilizing Local Potential - Nur 'Afifah, Luthfiana Sabila; Prajoko, Setiyo; Alamsyah, Muhammad Radian Nur (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
The city of Magelang has the local potential of the Kebun Bibit Senopati which has a variety of plants that can be used as teaching materials for plant diversity sub-materials. The potential diversity of Anthophyta plants in the Kebun Bibit Senopati can be packaged as a learning resource in the form of a web-module enrichment based on a scientific approach that is more practical and can be accessed anytime and anywhere. This study aims to determine the diversity of anthophytes in the Kebun Bibit Senopati, Magelang City, determine the feasibility of the enrichment web module, and determine the teacher's response to the enrichment web module. This research was carried out using the R&D method with a 4-D model which was limited to the development stage and modified by pre-experimentation. From the results of observations and identification of anthophytes in Kebun Bibit Senopati, it is known that there are 70 species of anthophytes that have been identified and grouped into 23 orders. The assessment of the feasibility of the web-enrichment module from media expert validators is 83.54%, material expert validators are 88.5%, and pedagogical expert validators are 81%. The feasibility of the web module is equipped with the results of the N-gain value, which is in the high category, which is effective as an enrichment learning teaching material. The teacher's response to the development of the web module is strongly agreed upon, accompanied by the acquisition of assessment results from the teacher of 85.83%. The enrichment web module is considered very feasible and effective to be used as teaching material in learning the enrichment of plant diversity sub-materials.